Genetic studies on growth and wool production traits in crossbred sheep of India - GUPTA, PARUL; CHAKRABORTY, DIBYENDU; DAS, A K; KUMAR, NISHANT; KHAN, NUSRAT (The Indian Journal of Animal Sciences, 2015)
Data on 5,435 lambs pertaining to 166 rams of Rambouillet and their crosses over the 13 years (1998–2010) at Government Sheep Breeding and Research Farm, Reasi, Jammu, were studied. The averages of birth weight (BWT), weaning weight (WWT), litter size (LS), greasy fleece weight (GFW), staple length (SL) and fiber diameter (FD) were 3.034±0.010 kg, 22.644±0.061 kg, 1.052±0.009, 1.520±0.009 kg, 5.599±0.019cm and 21.310±0.014 μ, respectively. The highest co-efficient of variation (CV) percentage was observed for greasy fleece weight whereas the lowest CV was observed for fiber diameter. The least-squares means were 3.088±0.023 kg, 22.578±0.148 kg, 1.046±0.007, 1.533±0.021 kg, 5.719±0.045cm and 21.315±0.034 μ for BWT, WWT, LS, GFW and FD, respectively. The effect of year of lambing was significant for all the traits under present study, whereas, the effect of season of lambing was nonsignificant for all the traits. The effect of sex was significant for growth traits and greasy fleece weight only. However, no systematic trend was observed over the year, season of lambing and sex for all the traits studied. The estimates of heritability were high for BWT (0.351), medium for WWT (0.301), GFW (0.401) and SL (0.453), whereas for FD and LS, it was low as 0.272 and 0.132, respectively. The genetic and phenotypic correlations were either negative or low. These estimates revealed that there is a scope for genetic improvement of these traits through appropriate selection methods.